Students Perception of Citizen Science's Contribution in Improving Scientific Argumentation Skills on Environmental Change and Sustainability Materials - Agung, Achmad; Mubaarak, Raaqa Alfath; Ramadani, Rima; Roviati, Evi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Citizen Science is considered a way to improve the relationship between research, education, and action by involving non-professionals in scientific research. Through Citizen Science, students will be trained to think critically and construct scientific arguments based on data and evidence they collect on their own. However, the scientific argumentation ability of students in several high schools in Region III of Cirebon is still relatively low. Based on the results of surveys and interviews with Biology teachers in the region, learning is still dominated by the Teacher-Centered approach, where the learning process is more teacher-centered. This research is a descriptive qualitative research conducted to determine students' perceptions of Citizen Science's contribution to scientific argumentation skills on environmental change and sustainability, using a descriptive method. The population in this study is MA and SMA in the Cirebon City/Regency area, while the schools sampled in this study are SMA Negeri 1 Source, SMA Negeri 8 Cirebon City, and MA Salafiyah Cirebon City. The data collection techniques used in this study are structured interview techniques and questionnaires, and based on questionnaires and interviews there are a variety of answers obtained, but in general many students are new to Citizen Science, and students' interest in agreeing to the Citizen Science hypothesis can improve scientific argumentation skills and critical thinking skills, in addition to the level of relevance between Citizen Science and environmental change and sustainability materials have great potential to be implemented.